Characterization of arbuscular mycorrhizal fungal species associating with Zea mays - Maússe-Sitoe, Sílvia; Dames, Joanna (Frontiers in Plant Science, 2024)
Taxonomic identification of Arbuscular Mycorrhizal (AM) fungal spores extracted directly from the field is sometimes difficult because spores are often degraded or parasitized by other organisms. Single-spore inoculation of a suitable host plant allows for establishing monosporic cultures of AM fungi. This study aimed to propagate AM fungal spores isolated from maize soil using single spores for morphological characterization. First, trap cultures were established to trigger the sporulation of AM fungal species. Second, trap cultures were established with individual morphotypes by picking up only one spore under a dissecting microscope and transferring it to a small triangle of sterilized filter paper, which was then carefully inoculated below a root from germinated sorghum seeds in each pot and covered with a sterile substrate. All pots were placed in sunbags and maintained in a plant growth room for 120 days. Spores obtained from single spore trap cultures from each treatment, maize after oats (MO), maize after maize (MM), maize after peas (MP), and maize after soybean (MS) were extracted using the sieving method. Healthy spores were selected for morphological analysis. Direct PCR was conducted by crushing spores in RNAlater and applying three sets of primer pairs ITS1 x ITS4; NS31 x AML2; SSUmcf and LSUmBr. Nucleotide sequences obtained from Sanger sequencing were aligned on MEGA X. The phylogenetic tree showed that the closest neighbors of the propagated AM fungal species belonged to the genus Claroideoglomus, Funneliformis, Gigaspora, Paraglomus, and Rhizophagus. The morphological characteristics were compared to the descriptive features of described species posted on the INVAM website, and it included Acaulospora cavernata, Diversispora spurca, Funneliformis geosporus, F. mosseae, Gigaspora clarus, G. margarita, Glomus macrosporum, Paraglomus occultum, and Rhizophagus intraradices. These findings can provide a great contribution to crop productivity and sustainable management of the agricultural ecosystem. Also, the isolate analyzed could be grouped into efficient promoters of growth and mycorrhization of maize independent of their geographical location.